The small worlds of corporate governance - Kogut, Bruce Mitchel (MIT Press, 2012)
The financial crisis of 2008 laid bare the hidden network of relationships in corporate governance: who owes what to whom and who will stand by whom in times of crisis. This book maps the influence of these types of economic and social networks on corporate behaviour and governance.